FACTORS AFFECTING STUDENTS’ ANXIETY IN SPEAKING FOR DAILY CONTEXT (A STUDY OF THE SECOND SEMESTER ENGLISH STUDENTS AT THE ENGLISH EDUCATION STUDY PROGRAM OF FATMAWATI SUKARNO ISLAMIC STATE UNIVERSITY IN ACADEMIC YEAR 2025/2026) - Ejontomi Afrizon; Rezky Atri Oktarin; Pahrozi Ahmad; Tania Syafutri (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
This study investigated the factors affecting students’ anxiety in speaking for daily context among second-semester students in an English Education Study Program. Speaking anxiety remains a common challenge in English as a Foreign Language (EFL) learning, particularly in spontaneous communication. The study aimed to identify the level of students’ speaking anxiety, determine the dominant contributing factors, and explore students’ experiences in everyday communication situations. A mixed-method design with an explanatory sequential approach was employed. Quantitative data were collected through a Likert-scale questionnaire administered to 32 students selected using purposive sampling. The data were analyzed using descriptive statistics, including mean scores and percentages. Qualitative data were obtained through semi-structured interviews and classroom observations and were analyzed using thematic analysis to provide deeper insights into students’ experiences. The findings showed that most students experienced high levels of speaking anxiety in daily contexts. Fear of negative evaluation was identified as the most dominant factor, followed by lack of confidence and limited vocabulary. In contrast, classroom environment and test anxiety were found to have a lower influence. Qualitative results indicated that students’ anxiety was closely related to fear of making mistakes, peer judgment, and difficulty expressing ideas. Observable behaviors such as hesitation, avoidance, and code-switching supported these findings. These results indicate that speaking anxiety in daily communication is primarily influenced by internal psychological and linguistic factors rather than external conditions, suggesting the need for greater attention to learners’ confidence and language readiness.